IDENTIFIKASI BORAKS DAN FORMALIN PADA MIE BASAH DALAM SOTO MIE - Angki Purwanti; Diah Lestari; Salbiah Salbiah (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Background: Dozen of soto mie culinary traders in the sub-district of Pondok Melati Bekasi always full of buyers. Preliminary test result using 3 samples of wet noodles which is obtained from culinary seller of soto mie in that area positively identified borax and formalin. Aims: The aim of thisresearch is to identify borax and formalin on wet noodles found in culinary soto mie in the sub-district of Pondok Melati Bekasi. Methods: The research sample was 22 packs of wet noodles obtained from 22 soto mie culinary traders in Pondok Melati sub-district, Bekasi. The borax test used the flame test methode and the curcumin paper test, while the formalin test uses chromotropic acid reagent and Schryvers reagent. Results: Identification of borax on wet noodles in culinary soto mie, by flame test and curcumin paper test resulted in 22 samples (100%) positive for borax. Identification of formalin in the same sample, using chromotropic acid and Schryvers reagent resulted in 22 samples (100%) positive for formalin. Conclusion: Wet noodles in culinary soto mie sold in the region Pondok Melati is all positive for borax and formalin